Optimization of Cardiorespiratory Fitness and Quality of Life in Women with Chronic Heart Failure after a Cardiac Rehabilitation Program - Briceño Gómez, Erik Eduardo; Lara Vargas, Jorge Antonio; Martínez Paniagua, José Leonardo; Radillo Alba, Hugo Alberto (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Women with heart failure (HF) tend to experience a greater symptom burden and lower quality of life, possibly due to phenotypic differences and unique gender-associated risk factors. Despite evidence on the effects of cardiac rehabilitation programs (CRP) in the general population, there is underrepresentation of women in these programs. Additionally, the impact of CRP on cardiorespiratory variables obtained through cardiopulmonary exercise testing (CPET) and health-related quality of life (HRQoL) in women with HF remains unknown. Objective: To assess the impact of a CRP on cardiorespiratory fitness (CRF) in cardiorespiratory variables obtained through CPET and HRQoL in women with HF. Methods: A quasi-experimental study included HF patients who completed a CRP from June 2019 to December 2023. The CRP involved nutritional assessment, psychosocial evaluation, educational sessions, and concurrent training. It comprised 30 minutes of aerobic resistance training at 65-80% of heart rate reserve (HRR) and 30 minutes of strength training at 30-50% of 1-repetition maximum (1RM), with a frequency of 3 sessions per week for 4 to 6 weeks. CPET was conducted at the beginning and end of the program, analyzing cardiorespiratory variables. HRQoL was assessed using the SF-36 questionnaire. Gains in CRF and HRQoL at the end of the program in both men and women were analyzed. Results: Out of 217 included patients, 29.9% were women. At the program's onset, women showed lower exercise tolerance than men (workload 5.4±2.57 METs vs. 6.62±2.53 METs) and worse HRQoL (62.03%±18.37 vs. 68.38%±18.37). However, post-intervention, they optimized their CRF (%predicted VO2 [%VO2p] initial 56.62%±20.11 vs final 80.12%±30.32, p=<0.001). Significant improvements in cardiorespiratory variables were observed in both cases: delta METs-load 3.02, p=<0.001, delta peak oxygen consumption (VO2peak) 1.83 ml/kg/min, p=<0.001, delta oxygen pulse (PO2) 1.21, p=0.021, delta cardiac power output (CPO) 1917, p=0.004, with a rightward shift in ventilatory thresholds and improvement in HRQoL (62.03%±18.37 vs. 78.81%±12.9, p=<0.001) post-CRP. The only variable with no significant changes in either case was VE/VCO2 slope (delta -0.51, p=0.736). Additionally, in women with reduced left ventricular ejection fraction (<50%), variables with no significant improvement included CPO (delta 959.22, p=0.283) and time to recovery of VO2 kinetics (TRCVO2) (delta -0.74, p=0.957). In patients with preserved left ventricular ejection fraction (≥50%), variables with no significant change included PO2 (delta 1.08, p=0.173), TRCVO2 (delta 26.82, p=0.099), and the first ventilatory threshold (VT1) (delta 0.09, p=0.504). Program attendance was 87.5% in both groups. Conclusion: Implementing a CRP in women with HF resulted in significant improvements in all evaluated cardiorespiratory variables (except for VE/VCO2 slope) and quality of life. These findings support the importance of ensuring women's access and participation in cardiac rehabilitation programs. Addressing existing barriers is crucial to maximize the long-term benefits of CRP in the female population with HF.